2005
DOI: 10.1128/aac.49.10.4009-4014.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Ciprofloxacin Dosing for Pseudomonas aeruginosa Infection by Using Clinical Outcome-Based Monte Carlo Simulations

Abstract: Pseudomonas aeruginosa causes serious infections whose outcome is highly dependent on antimicrobial therapy. The goal of this study was to predict the relative efficacies of three ciprofloxacin dosing regimens for P. aeruginosa infection using clinical outcome-based Monte Carlo simulations (MCS) with "real patient" demographics, pharmacokinetics, MICs, and pharmacodynamics (PDs). Each cohort consisted of 1,000 simulated study subjects. Three ciprofloxacin dosing regimens were studied, including (i) the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…However, P. aeruginosa was recovered in all patients treated, and a PK/PD analysis of bacteriological outcome has not been reported (154). These findings are in agreement with findings of other clinical tobramycin studies (164,209,210). Aerosolized administration of liposomal amikacin to CF patients did not result in a PK/PD-driven change in lung function tests, but a concentration-dependent reduction of bacterial load was correlated to the AUC/MIC ratio (170,171,222).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientssupporting
confidence: 82%
See 1 more Smart Citation
“…However, P. aeruginosa was recovered in all patients treated, and a PK/PD analysis of bacteriological outcome has not been reported (154). These findings are in agreement with findings of other clinical tobramycin studies (164,209,210). Aerosolized administration of liposomal amikacin to CF patients did not result in a PK/PD-driven change in lung function tests, but a concentration-dependent reduction of bacterial load was correlated to the AUC/MIC ratio (170,171,222).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientssupporting
confidence: 82%
“…Subsequent studies with ciprofloxacin confirmed that an AUC/ MIC ratio of Ն125 h was associated with clinical and bacteriological efficacy against highly susceptible P. aeruginosa isolates only (207)(208)(209)(210)(211). The probability of meeting the PK/PD target, i.e., an AUC/MIC ratio of Ն125 h for isolates with MICs of Ͼ0.3 mg/liter, was suboptimal, resulting in a target attainment rate of 53 to 59% for routinely isolated P. aeruginosa strains in 2002 (212).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 99%
“…allows for the prediction of antimicrobial effectiveness in patients whose physiological attributes are likely to be encountered under clinical conditions (Zelenitsky et al 2005;Drusano 2007). Once a numerical value for a PK/PD target has been defined (e.g.…”
Section: General Considerationsmentioning
confidence: 98%
“…To demonstrate the probability of target attainment, a study of three ciprofl oxacin dosing regimens against P. aeruginosa using clinical outcome-based Monte Carlo simulations showed higher ciprofl oxacin doses of 400 mg IV every 8 h should be used to ensure target attainment. However, as the authors conclude, even higher doses may be ineffective in ensuring target attainment as the MIC of offending pathogens approaches 1 mcg/mL [ 54 ]. Similarly, in a study of critically ill patients with severe community-acquired pneumonia undergoing mechanical ventilation, a levofl oxacin intravenous dose of 500 mg once daily achieved a C max /MIC of 10 or more and AUC 24 /MIC of at least 125 in both serum and epithelial lining fl uid when the MIC of the isolated pathogen was 1 mcg/mL or less.…”
Section: Human Datamentioning
confidence: 92%